Analysis of genetic factors influencing alpha-defensin gene expression - Necsoiu, Paula Eugenia (2018)
Background: The DEFA1A3 locus on chromosome 8p23.1 has been known to exhibit copy number variation (between 3 and 16 copies) and to include either the DEFA1 gene or the DEFA3 gene in any repeat. These two genes encode the Human Neutrophil Peptides HNPs 1-3, antimicrobial peptides implicated in the innate immune response. Objectives: The primary aim of this study was to determine whether there is any significant relationship between alpha defensin copy number and expression levels. The secondary aim was to understand more about 6836028G, a synonymous variant in exon 2 of the DEFA1A3 locus which affects a valine codon. Results and Conclusions: Levels of DEFA3 expression in mRNA are not simply proportional to genomic copy number; in cDNA DEFA3 appears to be expressed about 6-7 times more per copy than DEFA1. A similar relationship is also reflected in the variant 6836028G, which is underrepresented by a factor of about 1.4-fold in cDNA relative to genomic DNA; we assume that this variant might accompany only the DEFA1 gene, due to low levels of 6836028G in cDNA.